Urgensi Penerapan Asas Proporsionalitas Dalam Kontrak Elektronik Pinjaman Online - Beryl Alfarez Hertanto; Adi Sulistiyono (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This article aims to explore the urgency of applying the principle of proportionality in online loan agreements. The research results are expected to be utilized by all parties involved, especially prospective recipients of online loans, in crafting a standardized online loan agreement. The research methodology employs normative legal research, utilizing both primary and secondary legal materials through a literature review data collection technique. The approaches used in this research are the legislative approach (statute approach) and the conceptual approach. The data analysis technique employed is deductive analysis using the syllogism method. The application of the proportionality principle is examined through a guiding theory to identify the proportionality principles in contracts, including the principles of equality of rights, freedom, proportional distribution, and an elegant resolution with a win-win solution. Applying the proportionality principle in online loan electronic contracts is expected to minimize the risk of disputes during the execution of online loan agreements.